Plant Lectins as Medical Tools against Digestive System Cancers - Laura Elena Estrada-Martínez (International Journal of Molecular Sciences, 2017)
Digestive system cancers—those of the esophagus, stomach, small intestine, colon-rectum, liver, and pancreas—are highly related to genetics and lifestyle. Most are considered highly mortal due to the frequency of late diagnosis, usually in advanced stages, caused by the absence of symptoms or masked by other pathologies. Different tools are being investigated in the search of a more precise diagnosis and treatment. Plant lectins have been studied because of their ability to recognize and bind to carbohydrates, exerting a variety of biological activities on animal cells, including anticancer activities. The present report integrates existing information on the activity of plant lectins on various types of digestive system cancers, and surveys the current state of research into their properties for diagnosis and selective treatment.